(untitled) (Research, Society and Development, 2022)
Due to the growing and intense demand of the consumer for high quality food, in the last years, an amount of research has been focused on minimizing nutritional losses and remaining the fresh-like feature, often affected by conventional thermal treatment. Among the emerging technologies, high-pressure carbon dioxide (HP-CO2) has shown efficient results for food stabilization. Some disparities regarding the effect of process parameters in the treatment of foods with HP-CO2 were observed in the literature. Thus, in this work, the data found in a bibliographic survey were organized into the five most discussed in topics the consulted works: the thermodynamic state, temperature, pressure, CO2 ratio, and treatment time. In general, it was observed that enzymes and microorganisms have different resistance to process parameters, which can vary even longer with the change of environment components, the type of microorganism, or enzyme source. Therefore, results observed in a given food matrix may be different if the same treatment is applied to another different matrix.